SURVEY PENGGUNAAN BAHAN AJAR MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS SMAN 1 GEDANGAN SIDOARJO - GANIS ANISA NINGRUM (Jurnal Pendidikan Akuntansi (JPAK), 2013)
The purpose of study is to know the using of teaching material in SMAN 1 Gedangan and the decent of teaching material. The function of study can be used as reference material of using a teaching material in accounting class. The approach of study is descriptive study with quantity approach. The subject of study is accounting teacher of elevent social class, and the object of study is teaching material applied in the learning teaching process in eleventh social class. The results of this study are Festive materials used in SMAN 1 Gedangan a Module "Hayati Tumbuh Subur". The teaching material is choosen because the material has been fullfiled SK and KD in accounting learning class and the price the module is very cheap. Module in terms of the feasibility of the content, feasibility presentation, linguistic appropriateness, and graph feasibility that have been reviewed by the Expert Subjects declared eligible. Keywords : Teaching Materials